2017
DOI: 10.18632/oncotarget.18251
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LAG-3 defines exhaustion of intratumoral PD-1+ T cells and correlates with poor outcome in follicular lymphoma

Abstract: Exhausted T-cells in follicular lymphoma (FL) typically express PD-1, but expression of PD-1 is not limited to exhausted cells. Although expected to be functionally suppressed, we found that the population of intratumoral PD-1+ T cells were predominantly responsible for production of cytokines and granules. This surprising finding prompted us to explore the involvement of LAG-3 to specifically identify functionally exhausted T cells. We found that LAG-3 was expressed on a subset of intratumoral T cells from FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 30 publications
3
116
0
Order By: Relevance
“… 92 93 Such LAG-3-expressing T reg cells produce high levels of immunoregulatory cytokines IL-10 and TGF-β and suppress tumor-specific T cells. Consistently, the levels of LAG-3 expression and infiltration of LAG-3 + cells in tumors have been reported to be associated with tumor progression, poor prognosis, and unfavorable clinical outcomes in various types of human tumors, such as colorectal cancer, 94 renal cell carcinoma, 95 follicular lymphoma, 36 head and neck squamous cell carcinoma (HNSCC), 96 non-small cell lung cancer, 97 breast cancer, 98 and diffuse large B cell lymphoma. 99 These results strongly indicate that LAG-3 contributes to immune escape mechanisms in tumors similar to PD-1.…”
Section: Lag-3 In Antitumor Immunitymentioning
confidence: 76%
“… 92 93 Such LAG-3-expressing T reg cells produce high levels of immunoregulatory cytokines IL-10 and TGF-β and suppress tumor-specific T cells. Consistently, the levels of LAG-3 expression and infiltration of LAG-3 + cells in tumors have been reported to be associated with tumor progression, poor prognosis, and unfavorable clinical outcomes in various types of human tumors, such as colorectal cancer, 94 renal cell carcinoma, 95 follicular lymphoma, 36 head and neck squamous cell carcinoma (HNSCC), 96 non-small cell lung cancer, 97 breast cancer, 98 and diffuse large B cell lymphoma. 99 These results strongly indicate that LAG-3 contributes to immune escape mechanisms in tumors similar to PD-1.…”
Section: Lag-3 In Antitumor Immunitymentioning
confidence: 76%
“…Predicated on our previous studies demonstrating heterogeneity within PD-1 + cells of the lymphoma microenvironment ( Yang et al, 2012 , 2015 , 2017 ), we next focused on characterizing PD-1 + T cell phenotypes within FL using our CyTOF panel. In this cohort, approximately 71.5% of intratumoral CD3 + T cells expressed PD-1 with either low or high intensity ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these canonical T cell subsets, specific T cell subsets have recently been shown to play crucial roles in immunogenic dysregulation characteristic of certain disease states, such as cancer. For example, in B cell non-Hodgkin lymphoma, our group has identified involvement of TIM-3 + ( Yang et al, 2012 ) and LAG-3 + ( Yang et al, 2017 ) T cells in cytokine-induced T cell exhaustion and have demonstrated a role for CD70 + T cells in transforming growth factor β (TGF-β)-mediated T cell inhibition ( Yang et al, 2014 ) within the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma patients with a higher ratio of Vδ1 to total γδ T-cells had poorer overall survival and vice versa higher frequencies of Vδ2 cells were associated with longer survival in a study using CTLA4 inhibitory antibody ipilimumab ( 16 ). Expression of LAG-3 indicates inhibition of PD-1 + T-cells in the tumor tissue and poorer prognosis in follicular lymphoma ( 206 ). From studies examining distinctive T-cell populations, we know that CTLA4 can inhibit T-cell activity via signaling mechanisms distinctive from PD-1 ( 207 ), but we still lack mechanistic studies conclusively demonstrating CTLA4 expression and function for Vγ9Vδ2 T-cells.…”
Section: Targeting Activating and Inhibitory Receptorsmentioning
confidence: 99%